PARADIPLOMACY OF INDONESIAN SUB-STATE ACTOR: DIGITAL DIPLOMACY OF JAKARTA GOVERNMENT IN RESPONSE TO COVID-19 - Luerdi Luerdi (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
The outbreak of COVID-19 has caused challenges to international affairs in term of health, economy, politics and security in addition to the changes of interaction between actors. As one of the regional governments in a unitary state and a capital city of Indonesia, the Jakarta government projected its paradiplomacy in response to the pandemic. Its status as a lower administration under the national government did not prevent it from taking active efforts by exploiting internet and digital technology development. The paper aims to describe the Jakarta government’s paradiplomatic practices in responding to the COVID-19. This research applied the qualitative method with a descriptive analysis. In addition, this research employed the concept of paradiplomacy and digital diplomacy. The findings show that the Jakarta government carried out digital diplomacy as the form of its paradiplomacy in a number of activities such as providing reliable information, collaborating with foreign communities, participating in global forum, releasing gubernatorial message, improving data platform capability and initiating an international forum at home. Such internet-supported activities were meant to share experience, collaborate and provide transparency. Paradiplomacy in the form of digital diplomacy activities was mainly conducted to gain trust to the regional government from its international audiences and create an image that Jakarta was a crisis-proof city and the part of global community. The paper argues that sub-national governments’ roles in international affairs are becoming important thanks to a new room for diplomacy practices, strengthened by unprecedented global crises.